PENGARUH BUDAYA PATRIARKI TERHADAP MARAKNYA CATCALLING - anita puspita; wildan nugraha (UHN IGB Sugriwa Denpasar, 2023)
A patriarchal culture is created when people believe that men should hold the highest positions. The perception that men hold the highest position indirectly forms a patriarchal culture. This reveals to the conclusion that catcalling is accepted as normal. Even though catcalling is like a compliment, there is a significant difference between the two. Compliments are given sincerely, whereas catcalling aims to indirectly harass women. The purpose of this research is to provide information and advice regarding the prevalence of catcalling in public places, especially among women. Qualitative method is the method used to complete this research. A total of 54 students were involved as respondents in this study to collect statistical data. The statistical information is used to gauge how well students comprehend the catcalling phenomena. Based on the results of a survey conducted online via Google form, shows that the majority of victims of catcalling are women. In addition, 96% of respondents understand what is meant by the phenomenon of catcalling. About 81% consider catcalling to be annoying and disturbing. On the other hand, as many as 57% of respondents stated that catcalling was caused by the attachment to patriarchal culture. On the other hand, 43% of respondents said that catcalling was caused by the way women dress. Based on the research results, the authors argue that almost all students understand the phenomenon of catcalling. Furthermore, the authors conclude that every tertiary institution needs to provide an understanding of the catcalling phenomenon that comes from patriarchal culture.